Adaptation of plants to high-calcium content kart regions: possible involvement of symbiotic microorganisms and underlying mechanisms - Li,F. (2020)
Abstract Rhizosphere microorganisms and endophytes can help their hosts absorb nutrients and regulate the levels of plant hormones. Moreover, they can modulate the expressions of host genes, assist hosts in eliminating reactive oxygen species (ROS) and secreting volatile organic compounds. Therefore, rhizosphere microorganisms and endophytes are considered as determinant factors driving processes involved in the growth of host plants. However, the physiological and ecological functions, as well as the molecular mechanism underlying the behavior of rhizosphere microorganisms and endophytes in their role in the adaptive capacity of host plants in the karstic high-calcium environment have not been systematically studied. This review summarizes the physiological and molecular mechanisms of rhizosphere microorganisms and endophytes which help host plants to adapt to various kinds of adverse environments. The adaptive capacities of plants growing in adverse environments, partly, or totally, depends on microorganisms co-existing with the host plants.